The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1097/tp.0000000000004138
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation in Hepatitis B/Hepatitis D (Delta) Virus Coinfected Recipients

Abstract: Hepatitis D is caused by the hepatitis D virus (HDV); it is the most severe form of viral hepatitis in humans, running an accelerated course to cirrhosis. There is no efficacious therapy, and liver transplantation provides the only therapeutic option for terminal HDV disease. However, HDV infection is prevalent in poor countries of the world with no access to liver transplant programs; liver grafting has been performed in high-income countries, where the prevalence of the infection has much diminished as a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…hDV вызывает более быстрое прогрессирование заболевания печени, чем один только hbV. приблизительно от 30 до 70% пациентов с hDV на момент постановки диагноза имеет цп, и более 50% умирает от заболевания печени в течение 10 лет после постановки диагноза [12]. однако недавние исследования показали, что прогрессирование варьируется и что более 50% людей может иметь вялотекущее течение.…”
Section: заключениеunclassified
“…hDV вызывает более быстрое прогрессирование заболевания печени, чем один только hbV. приблизительно от 30 до 70% пациентов с hDV на момент постановки диагноза имеет цп, и более 50% умирает от заболевания печени в течение 10 лет после постановки диагноза [12]. однако недавние исследования показали, что прогрессирование варьируется и что более 50% людей может иметь вялотекущее течение.…”
Section: заключениеunclassified
“…In a European Transplant Registry, with 1939 transplants for HDV reported from 1988 to 2016, although there was a significant decline over time in the number of HBV transplants, there was a much lower rate of decline in HDV transplants, suggesting that advanced disease as a result of lack of effective therapies may be leading to advanced disease necessitating transplant 33 . Although HDV recurrence in transplant recipients has been described, contemporary approach to post‐transplant prophylaxis with nucleoside analogue and HBIG appears to be highly effective in providing virologic control 34 …”
Section: Hdv Disease Characteristics and Disease Progressionmentioning
confidence: 99%
“…33 Although HDV recurrence in transplant recipients has been described, contemporary approach to post-transplant prophylaxis with nucleoside analogue and HBIG appears to be highly effective in providing virologic control. 34 In addition to clinical outcomes, patient-reported outcomes (PROs) have also been evaluated among individuals with HDV. In a study conducted in Spain evaluating PROs among HDV versus HBV mono-infected patients, patients with chronic HDV scored worse on the worry score, functional well-being score and the activity impairment score compared to patients with chronic HBV.…”
Section: Hdv D Is E a S E Char Ac Teris Ti C S And Dise A Se Prog Re ...mentioning
confidence: 99%
“…7 Nonetheless, some studies have shown that HDV may protect against HBsAg recurrence after LT 8 and that HBV suppression with NAs would prevent full HBV reactivation, precluding HDV recurrence. 9,10 The latter would imply that life-long HBIG administration may not be necessary.…”
Section: Backg Round and Aimsmentioning
confidence: 99%
“…To prevent HBsAg reappearance, which may in turn facilitate relapse of hepatitis D, most experts recommend lifelong prophylaxis 7 . Nonetheless, some studies have shown that HDV may protect against HBsAg recurrence after LT 8 and that HBV suppression with NAs would prevent full HBV reactivation, precluding HDV recurrence 9,10 . The latter would imply that life‐long HBIG administration may not be necessary.…”
Section: Background and Aimsmentioning
confidence: 99%